Presidio y población indígena. Siglos XVII y XVIII - Guevara Sánchez, Arturo (Universidad Michoacana de San Nicolás de Hidalgo, 2011)
For their characteristics and for their distance of the entrance ports, the European colonization of New Biscay was much later that that of the center of the viceroyalty. The discovery of mining locations was maybe as important as those of Zacatecas and Guanajuato, but great part of the Europeans they chose avecindarse far from the mines. They made this to transform into farmers and to make the livestock upbringing. This phenomenon seems to be had quick after the establishments of the Franciscans of the XVII Century.1 when they were still far from New Biscay, the Spaniards already believed to be entitled full to have America.2 this was an idea of those that later on the father Francisco of Vitoria, a very grateful theologian, had opportunity to rebut it.3 their argument was overwhelming; it was true that Columbus' trips had allowed him/her to make the casual discovery of the continent but in spite of such a luck, it concluded in that according to the natural right, the King could not have the recently discovered earth because he had for owners to the Indians.

Por sus características y por su lejanía de los puertos de entrada, la colonización europea de la Nueva Vizcaya fue mucho más tardía que el del centro del virreinato. El hallazgo de yacimientos mineros fue quizás tan importante como los de Zacatecas y Guanajuato, pero gran parte de los europeos eligieron avecindarse lejos de las minas. Hicieron esto para convertirse en agricultores y hacer la crianza de ganado. Este fenómeno parece haberse acelerado después de los asentamientos de los franciscanos del Siglo XVII.1 Cuando todavía estaban lejos de la Nueva Vizcaya, los españoles ya creían tener pleno derecho a disponer de América.2 Esta fue una idea de aquellas que posteriormente el padre Francisco de Vitoria, un teólogo muy reconocido, tuvo oportunidad de rebatirla.3 Su argumentación fue contundente; era verdad que los viajes de Colón le habían permitido hacer el descubrimiento casual del continente pero a pesar de tal suerte, concluyó en que de acuerdo al derecho natural, el Rey no podía disponer de la tierra recién descubierta porque tenía por dueños a los indios.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Doctorado en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-D-2011-0002; Presidio; Población indígena; Nueva Vizcaya; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2085